Androgenic pathway in triple negative invasive ductal tumors: Its correlation with tumor cell proliferation. Issue 5 (15th March 2013) - McNamara, Keely M.; Yoda, Tomomi; Miki, Yasuhiro; Chanplakorn, Niramol; Wongwaisayawan, Sansanee; Incharoen, Pimpin; Kongdan, Youwanush; Wang, Lin; Takagi, Kiyoshi; Mayu, Takagi; Nakamura, Yasuhiro; Suzuki, Takashi; et al.
<x xml:space="preserve">Abstract</x> Triple negative breast cancer (TNBC) is defined by estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 negativity. Patients with TNBC frequently undergo an aggressive clinical course due to the unavailability of specific targeted therapies. Androgen receptor (AR) was reported to be expressed in up to 60% of TNBC cases but there have been controversies as to the roles of androgen signaling through AR in TNBC. Therefore, in this study, we analyzed the status of AR in combination with androgen synthesizing enzymes (5α‐reductase type 1 (5αR1) and 17β‐hydroxysteroid dehydrogenase type 5 (17βHSD5)] in order to further understand androgenic actions in TNBC. Androgen receptor, 5αR1, and 17βHSD5 were immunolocalized in a cohort of 203 TNBC patients from Thailand and Japan. We then correlated the findings with clinicopathological characteristics (age, stage, tumor diameter, lymph node invasion, metastatic spread, Ki‐67 labeling index, disease‐free survival, and overall survival) of the patients. Univariate analysis revealed that AR+/enzyme+ cases were associated with a significantly lower Ki‐67 labeling index than AR−/enzyme− samples. Multivariate analysis indicated the presence of significant positive correlations between AR and enzyme status in tumor cells, and between tumor diameter, lymph node invasion, and distant metastasis. Significant negative correlations were also detected between Ki‐67 labeling index and AR status (P = 0.04) or 5αR1 (P < 0.001). Cox proportional hazards analysis showed that Ki‐67 labeling index and stage were the only factors predicting disease‐free and overall survival of the patients, although univariate Kaplan–Meier analysis revealed AR/5αR1 negativity suggested a more adverse clinical course up to 80 months after surgery. These results suggest that the presence of androgen synthesizing pathways in addition to AR expression in tumor cells could confer a better clinical outcome through suppression of cell proliferation.